2000
DOI: 10.1021/es0009830
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thermal Treatment on Mineralogy and Heavy Metal Behavior in Iron Oxide Stabilized Air Pollution Control Residues

Abstract: Stabilization of air pollution control residues by coprecipitation with ferrous iron and subsequent thermal treatment (at 600 and 900 °C) has been examined as a means to reduce heavy metal leaching and to improve product stability. Changes in mineralogy and metal binding were analyzed using various analytical and environmental techniques. Ferrihydrite was formed initially but transformed upon thermal treatment to more stable and crystalline iron oxides (maghemite and hematite). For some metals leaching studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 34 publications
6
36
0
3
Order By: Relevance
“…If Pb was confined inside an iron oxide structure, it presumably would only be released as the iron is released. This is consistent with the study performed by Sørensen et al, 13 who found Pb to be associated with the particle surface of an SD APC residue and an FA treated with the Ferrox process. Furthermore, Sørensen et al 13 mention that, in general, Pb 2+ cannot be incorporated in crystalline iron oxides because of the larger radius of the Pb 2+ ion.…”
Section: Leaching From Solidssupporting
confidence: 93%
See 3 more Smart Citations
“…If Pb was confined inside an iron oxide structure, it presumably would only be released as the iron is released. This is consistent with the study performed by Sørensen et al, 13 who found Pb to be associated with the particle surface of an SD APC residue and an FA treated with the Ferrox process. Furthermore, Sørensen et al 13 mention that, in general, Pb 2+ cannot be incorporated in crystalline iron oxides because of the larger radius of the Pb 2+ ion.…”
Section: Leaching From Solidssupporting
confidence: 93%
“…This is consistent with the study performed by Sørensen et al, 13 who found Pb to be associated with the particle surface of an SD APC residue and an FA treated with the Ferrox process. Furthermore, Sørensen et al 13 mention that, in general, Pb 2+ cannot be incorporated in crystalline iron oxides because of the larger radius of the Pb 2+ ion. However, it is possible that Pb is associated with another phase formed during the treatment process.…”
Section: Leaching From Solidssupporting
confidence: 93%
See 2 more Smart Citations
“…6 and 7 were prepared on the basis of their work, and we can conclude that S/S technology Ferrihydrite was formed initially but converted upon thermal treatment into more stable and crystalline compounds (maghemite and hematite). However, the overall effect of the Ferrox process followed by thermal treatment is an initially more contaminated leachate but the product obtained is more stable in the long term Sorensen et al (2000) ESP is at present in the maturing phase (Fig. 6), with a number of research projects aiming at optimizing the process.…”
Section: Solidification/stabilization (S/s)mentioning
confidence: 99%